Defensive Behavior in Rhinella bergi and Rhinella mirandaribeiroi (Anura: Bufonidae) - Nehemy, Ibrahim Kamel Rodrigues; Mângia, Sarah; Carvalho, Priscila Santos [UNESP]; Santana, Diego José (Universidad Nacional de Colombia, 2022)
Here we report two cases of defensive behavior known as “stiff-legged”, unprecedented for the species Rhinella bergi and R. mirandaribeiroi. We registered the behavior at localities in Mato Grosso do Sul and Minas Gerais states, Brazil. With our records, there are now five species from open areas that exhibit this behavior. We assume that the species that inhabit these areas exhibit this avoiding predation behavior simulating a dead body on the ground, behavior known as “death feigning”, unlike forest species, which use this strategy to camouflage themselves between the leaves.
Comportamiento defensivo en Rhinella bergi y Rhinella mirandaribeiroi (Anura: Bufonidae)
Keywords: Amphibians; defensive strategy; stiff-legged posture